The Interaction Efficiency of XPD-p44 With Bulky DNA Damages Depends on the Structure of the Damage - Petruseva, Irina; Naumenko, Natalia; Kuper, Jochen; Anarbaev, Rashid; Kappenberger, Jeannette; Kisker, Caroline; Lavrik, Olga (Frontiers in Cell and Developmental Biology, 2021)
The successful elimination of bulky DNA damages via the nucleotide excision repair (NER) system is largely determined by the damage recognition step. This step consists of primary recognition and verification of the damage. The TFIIH helicase XPD plays a key role in the verification step during NER. To date, the mechanism of damage verification is not sufficiently understood and requires further detailed research. This study is a systematic investigation of the interaction of ctXPD (Chaetomium thermophilum) as well as ctXPD-ctp44 with model DNAs, which contain structurally different bulky lesions with previously estimated NER repair efficiencies. We have used ATPase and DNA binding studies to assess the interaction of ctXPD with damaged DNA. The result of the analysis of ctXPD-ctp44 binding to DNA containing fluorescent and photoactivatable lesions demonstrates the relationship between the affinity of XPD for DNAs containing bulky damages and the ability of the NER system to eliminate the damage. Photo-cross-linking of ctXPD with DNA probes containing repairable and unrepairable photoactivatable damages reveals differences in the DNA interaction efficiency in the presence and absence of ctp44. In general, the results obtained indicate the ability of ctXPD-ctp44 to interact with a damage and suggest a significant role for ctp44 subunit in the verification process.